Unknown Hymnal of the Bernardine Order in Radom Preserved in the Diocesan Library in Sandomierz. The Content of the Manuscript - Trościński, Grzegorz (Piśmiennictwo zakonne w dobie staropolskiej, 2013)
This article is dedicated to an unknown hymnal which was discovered in the Diocesan Library in Sandomierz.It belonged earlier to the Bernardine Order in Radom. After the liquidation of the order in 1864, thehymnal arrived at Sandomierz together with the library of Franciscan Brothers Observantines.The study focuses on the content of this manuscript, dating back from the end of the seventeenth century,in order to show its uniqueness against the background of a couple of other preserved Bernardinehymnals.This discovered manuscript contains 164 works (some in fragments), a number of them with musicalnotes. The material includes literary works from the fifteenth until the eighteenth century. The mostnumerous in the collection are carols and songs about the Blessed Virgin. There are also Advent songs,Easter songs, songs about saints and picaresque songs. The texts in the manuscript are written in Latinand Polish; some of them are anonymous, while others were written by well-known authors (e.g. JanKochanowski’s psalms, religious works by Andrzej Krzycki, Jan Żabczyc and S. S. Jagodyński).The content of the manuscript corresponds with the contents of other Bernardine hymnals from the16th century: the Kórnik hymnal and the Puławy hymnal. Additionally, it includes unknown works orthose which so far have been known only from single records. The Bernardine hymnal from Radom isimportant evidence in the history of Bernardine songs in the Polish language. It extends our knowledgeby new editions of medieval works, e.g. Skarga umierającego [Lament of a Dying Man] or Satyra na leniwych chłopów [A Satire on Lazy Peasants].